Pertanggungjawaban Korporasi PT Kalimantan Ferro Industry Terhadap Kerusakan Lingkungan Sekitar Kawasan Industrinya Tahun 2023 - Nasir, Tomi Khoyron; Triadi, Irwan (Universitas Medan Area, 2024)
This research aims to discuss the chronology of criminal acts of environmental pollution of ditches by PT Kalimantan Ferro Industry regarding the impact of environmental damage and the corporate accountability mechanism of PT Kalimantan Ferro Industry to resolve cases of ditch pollution in the surrounding environment. This research uses a normative juridical method sourced from secondary data. The research compares Law No. 32 of 2009 concerning Environmental Protection and Management with Article 88 of the Job Creation Law in Corporations, which eliminates absolute responsibility for corporate violations to protect the environment. The author analyzed the environmental problems caused by PT KFI's waste water management installation and the accountability mechanism for this case based on the perspective of the Job Creation Law in Corporations, which is known to have changed the rules regarding absolute responsibility for corporations. The results of this research show that corporate responsibility for waste pollution is now limited to administrative-level responsibility after the abolition of absolute responsibility.